Otimização de produção de biomassa para extração lipídica utilizando estirpes da microalga Scenedesmus sp. - Oliveira, Flávia Costa (2019)
Species of microalgae such as Scenedesmus sp. have high potential for lipid accumulation in their cells, which makes feasible studies aimed at the exploitation of these organisms as raw material for the production of biodiesel. Among the variables that may interfere with the cultivation, diverse factors directly influence the metabolic storage of microalga nutritional reserves. When developing an optimized culture medium for the production of bio-oil extracted from microalgae it is important to investigate methodologies that increase biomass cropping and harvesting systems. This study was developed looking for evaluating which techniques of the microalgae Scenedesmus sp. allows a greater production of bio-oil. The cultivation took place in horizontal flat acrylic reactors, kept at room temperature to 25 ° C ± 1°C, with photoperiod controller in 12 hours of light and 12 hours of darkness, using three white fluorescent lamps of 40 Volts. The culture medium, time and inoculum percentage were the variables optimized for algal growth and lipid yield, in order to minimize the number of experiments performed and the time spent using factorial design 23 and central composite desing. The analyzes indicated that the experimental methodology for cultivation of microalgae Scenedesmus sp., Presented better yields in the lipid content, when submitted to cultivation in Chu medium with 20% of initial inoculum. However, it is observed that lipid accumulation reaches a maximum value when the initial concentration of Chu medium is approximately 39.5%. It was also verified that the number of days (time) presented a maximum point, indicating the tendency of higher lipid accumulation in 20 days of cultivation. For these conditions of initial concentration of Chu medium (39.5%) and cultivation time (20 days), the model predicts an accumulation of lipid content of approximately 9.74%.